Aplikasi BINDO TURU (Bahasa Isyarat Indonesia Tunarungu) Berbasis Android Sebagai Penunjang Pembelajaran Bahasa Isyarat Bagi Penyandang Disabilitas Tunarungu dan Masyarakat Awam Di Era Revolusi Industri 4.0 - Yoannes Romando Sipayung; Iwan Setiawan Wibisono (Multimatrix, 2020)
Abstract - Deafness, deafness, or hearing loss are a physical condition characterized by a decrease or a person's ability to hear. Communication for people who are deaf is using sign language. Communication will run smoothly if it is carried out by fellow deaf people. However, communication will not go well if it is done directly with normal people. This is a problem for both deaf and normal people. One of the ways that the general public can communicate with deaf people is by providing Android-based Indonesian sign language learning. The android application, named Bindo Turu (Sign Language for Deaf Indonesians), contains general materials in everyday life. In addition to the general public, this application is also intended for deaf people to make it easier to learn sign language.Keywords:Â  Deaf, Sign Language, Android Application